Numerical Assessment of Solar System Including Trombe Wall and Photovoltaic Module - E. Azizi; H. Safarzadeh (Journal of Applied and Computational Mechanics)
In current study, a model is developed for a one-story building with specific dimensions, integrating photovoltaic panels and Trombe walls to generate electricity and reduce energy consumption. The location chosen for the study is Kermanshah, using real climate data from the Meteonorm software to ensure accuracy. The proposed system is constructed using the TRNSYS dynamic simulation program, supplemented by a plugin for simulating the building's physical properties. The goal is to analyze the power output of the panels, their energy efficiency, airflow velocity through the channel, and the building's exergy change resulting from the addition of the Trombe wall. Additionally, a parametric analysis is scrutinized over the previous year to examine the efficacy of duct depth on various functional aspects of the system. The findings reveal that the solar panels reach their peak power generation during July and August, with a highest output of 207 kW. The exergy efficiency of the panels consistently exceeds their energy efficiency across different months, reaching up to 20% and 22%, respectively. Moreover, incorporating a Trombe wall leads to a 3% decrement in the building's cooling and heating load, with exergy efficiency peaking at a wall depth of 10 (cm). Increasing the channel depth is found to decrease the heating requirement while improving airflow through the channel.